Sim1 is required for the migration and axonal projections of V3 interneurons in the developing mouse spinal cord - Blacklaws, Jake (2015)
V3 spinal interneurons (INs) are a group of excitatory INs that play a crucial role in producing balanced and stable gaits in vertebrate animals. In the developing mouse spinal cord, V3 INs arise from the most ventral progenitor domain and form anatomically distinctive subpopulations in adult spinal cords. They are marked by the expression of transcription factor Sim1 postmitotically, but the function of Sim1 in V3 development remains unknown. Here, we used Sim1(Cre) ;tdTomato mice to trace the fate of V3 INs in a Sim1 mutant versus control genetic background during development. In Sim1 mutants, V3 INs are produced normally and maintain a similar position and organization as in wild types before E12.5. Further temporal analysis revealed that the V3 INs in the mutants failed to migrate properly to form V3 subgroups along the dorsoventral axis of the spinal cord. At birth, in the Sim1 mutant the number of V3 INs in the ventral subgroup was normal, but they were significantly reduced in the dorsal subgroup with a concomitant increase in the intermediate subgroup. Retrograde labeling at lumbar level revealed that loss of Sim1 led to a reduction in extension of contralateral axon projections both at E14.5 and P0 without affecting ipsilateral axon projections. These results demonstrate that Sim1 is essential for proper migration and the guidance of commissural axons of the spinal V3 INs.